La Castañeda Insane Asylum Narratives of Pain in Modern Mexico - Rivera garza , Cristina (2020)
"La Castañeda Insane Asylum is the first inside view of the workings of La Castañeda General Insane Asylum-a public mental health institution founded in Mexico City in 1910 only months before the outbreak of the Mexican Revolution. It links life within the asylum's walls to the radical transformations brought about as Mexico entered the Revolution's armed phase and then endured under succeeding modernizing regimes. Author Cristina Rivera Garza brings the history of La Castañeda asylum to life as inmates, doctors, relatives, and others engage in dialogues on insanity. They discuss faith, sex, poverty, loss, resentment, envy, love, and politics. Doctors translated what they heard into the emerging language of psychiatry, while inmates conveyed their personal experiences and private histories through expressions of mental suffering. The language of pain-physical and spiritual, mild to excruciating-allowed patients to detail the sources and consequences of their misfortune. Available now for the first time in English, this edition contains updated sources and features a note by the translator, Laura Kanost. "